2020
DOI: 10.1111/evo.14099
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of song structure to phylogenetic history, habitat, and morphology in the vireos, greenlets, and allies (Passeriformes: Vireonidae)

Abstract: Acoustic signals show immense variation among passerines, and several hypotheses have been proposed to explain this diversity. In this study, we tested, for the first time, the relationships of song structure to phylogeny, habitat type, and morphology in the vireos and allies (Vireonidae). Every measure of song structure considered in this study had moderate and significant phylogenetic signal. Furthermore, two song-constraining morphological traits, bill shape and body mass, also exhibited significant phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 147 publications
2
29
0
Order By: Relevance
“…The craniomandibular complex of birds, especially the beak, constitutes an all‐in‐one tool used for multiple tasks, including preening (Bush & Clayton, 2018), vocal modulation (Mejías et al, 2020), nest building (Hansell, 2000), thermoregulation (Tattersall et al, 2009), displaying behaviors (Murphy et al, 2009), intra‐ or interspecific fighting (Rico‐Guevara et al, 2019), and, most obviously, foraging and feeding (Beecher, 1951; Demmel Ferreira et al, 2019; Tokita et al, 2017). As such, ecomorphological variation and evolution of the skull and lower jaw are expected to be multifactorial in nature, being the outcome of several adaptive trade‐offs, as well as phylogenetic and/or developmental constraints (Bright et al, 2019; Navalón et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The craniomandibular complex of birds, especially the beak, constitutes an all‐in‐one tool used for multiple tasks, including preening (Bush & Clayton, 2018), vocal modulation (Mejías et al, 2020), nest building (Hansell, 2000), thermoregulation (Tattersall et al, 2009), displaying behaviors (Murphy et al, 2009), intra‐ or interspecific fighting (Rico‐Guevara et al, 2019), and, most obviously, foraging and feeding (Beecher, 1951; Demmel Ferreira et al, 2019; Tokita et al, 2017). As such, ecomorphological variation and evolution of the skull and lower jaw are expected to be multifactorial in nature, being the outcome of several adaptive trade‐offs, as well as phylogenetic and/or developmental constraints (Bright et al, 2019; Navalón et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of morphological divergence and similar plumage patterns have been recognized among most species (Hamilton, 1962), postulating that ecological differences could have been a mode of speciation in Vireo (Hamilton, 1959;1962;Barlow 1980). Additionally, a recent study found phylogenetic history strongly shapes song structure and morphology among vireos (Mejías et al, 2020). Several cryptic species have been rectified from species complexes within Vireo, including Hutton's vireo, Vireo huttoni (Cassin, 1851) (Cicero & Johnson, 1992), blue-headed vireo, Vireo solitarius (Wilson, 1810) (Johnson, 1995;Cicero & Johnson, 1998), and red-eyed vireo, Vireo olivaceus (Linnaeus, 1766) (Slager et al, 2014;Battey & Klicka, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Vireo (Vieillot, 1808) (Order: Passeriformes; Family: Vireonidae) contains 34 species and is found throughout the New World (Gill & Donsker, 2019). Thirteen species breed in North America, occupying a mosaic of habitats including temperate and boreal forests, shrublands, and woodland edges (Gill & Donsker, 2019; Mejías et al ., 2020). Reduction of morphological divergence and similar plumage patterns have been recognized among most species (Hamilton, 1962), postulating that ecological differences could have been a mode of speciation in Vireo (Hamilton, 1959; 1962; Barlow 1980).…”
Section: Introductionmentioning
confidence: 99%
“…However, even in some of the best‐studied groups, such as birds, there is mixed evidence for the role of sensory drive in signal evolution (Boncoraglio and Saino 2007; Mejías et al. 2020; Mikula et al. 2021).…”
mentioning
confidence: 99%
“…Sensory drive shapes signal evolution and diversification in several animal groups, such as insects (Rutowski et al 2007), fishes (Endler 1980), birds (Morton 1975), and mammals (Ey et al 2009). However, even in some of the best-studied groups, such as birds, there is mixed evidence for the role of sensory drive in signal evolution (Boncoraglio and Saino 2007;Mejías et al 2020;Mikula et al 2021). This mixed evidence may result from trade-offs between different selective pressures and how they play out across species.…”
mentioning
confidence: 99%